2008
DOI: 10.1148/radiol.2461070200
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Digital versus Film Mammography: Exploratory Analysis of Selected Population Subgroups in DMIST

Abstract: Purpose:To retrospectively compare the accuracy of digital versus film mammography in population subgroups of the Digital Mammographic Imaging Screening Trial (DMIST) defined by combinations of age, menopausal status, and breast density, by using either biopsy results or follow-up information as the reference standard. Materials andMethods:DMIST included women who underwent both digital and film screening mammography. Institutional review board approval at all participating sites and informed consent from all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
231
3
14

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 404 publications
(255 citation statements)
references
References 10 publications
7
231
3
14
Order By: Relevance
“…The ratio in sensitivity of digital mammography between younger and older women may be different due to improved sensitivity associated with digital mammography for younger but not for older women. 17 The estimated difference in sensitivity may therefore be overestimated and the number of additional LYG by screening before age 50 could be a conservative estimate. Model outcomes were also sensitive to the assumed trend in background breast cancer incidence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ratio in sensitivity of digital mammography between younger and older women may be different due to improved sensitivity associated with digital mammography for younger but not for older women. 17 The estimated difference in sensitivity may therefore be overestimated and the number of additional LYG by screening before age 50 could be a conservative estimate. Model outcomes were also sensitive to the assumed trend in background breast cancer incidence.…”
Section: Discussionmentioning
confidence: 99%
“…30 The PPV for women aged 40 to 49 was assumed to be 12% (40% of the PPV for women aged 50 and older). 17,32,33 In the Netherlands, mammography is often repeated in the hospital after recall for further assessment because of a suspicious screening mammogram. 34 Therefore, we assumed that all women recalled for further assessment would undergo an additional (diagnostic) mammogram.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…This result needs attention because breasts with high fraction of dense tissue are difficult to evaluate with mammography owing to the complex anatomical structures that affect the lesion detectability. Digital mammography is significantly better than film-screen conventional mammography in women with dense breasts [19]. In dense-breast images, the very low contrast between cancer and complex anatomical background can be overcome in part by the image processing, exploiting the high dynamic range of the digital detectors.…”
Section: Discussionmentioning
confidence: 99%
“…Digital mammographic imaging screening trial (DMIST) [16] found digital mammography had significant increase in performance in younger women with dense breasts, while film based mammography performed better in women aged 65 years or older and with fatty breasts. Similar results were found by Pisano et al (10) who found higher detection levels by FFDM in patients less than 50 years with dense breasts.…”
Section: Discussionmentioning
confidence: 99%